Content Marketing, Social Media Marketing and Search Engine Optimization (SEO) on Successful Business Performance in Msmes in Cirebon City with Digital Literacy as an Intervening Variabl - Sudadi Pranata; Umi Narimawati; M. Yani Syafei (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
In the digital era that continues to develop, the role of information technology and the internet increasingly dominates various aspects of life, including the business world. In particular, Micro, Small and Medium Enterprises (MSMEs) in Cirebon City need to continue to adapt to these changes in order to maintain and improve their business performance. The three main strategies to focus on in this context are Content Marketing, Social Media Marketing, and Search Engine Optimization (SEO). The aim of this research is to examine the influence of content marketing on digital literacy, social media marketing on digital literacy, search engine optimization (SEO) on digital literacy and digital literacy on business performance among MSMEs in the city of Cirebon. This research was conducted on micro, small and medium enterprises (MSMEs) in the Cirebon City area by giving questionnaires to business owners and MSME managers. The West Java Cooperatives and UMKM Service said that there were 21,939 MSMEs in Cirebon City. The Slovin formula was used to determine the sample size for this study. The sampling limit percentage that can still be tolerated is (0.1). So there were at least 96 people who answered the survey. Partial Least Square (PLS) model analysis was used in this research. The results of this research are that content marketing has no effect on MSME business performance, digital literacy has an effect on MSME business performance, social media marketing has an effect on MSME business performance and search engine optimization has an effect on MSME business performance.